How we can win : race, history and changing the money game that's rigged - Jones, Kimberly (Kimberly Latrice) (UK: Text Publishing Melbourne Australia, 2022)
"A breakdown of the economic and social injustices facing Black people and other marginalized citizens inspired by political activist Kimberly Jones' viral video, "How Can We Win.""--
How can we win? -- Hood girls can be heroes too -- Four hundred rounds of Monopoly -- Reconstruction -- The game is fixed -- How we can win -- Reconstruction 2.0 -- Nine priorities for a balanced life -- Hope looks like the future.
Includes bibliographical references.
Keywords: Jones, Kimberly; African Americans -- Social conditions; African Americans -- Economic conditions